Effect of different types of emulsifiers on the physical characteristics and fat bloom stability of dark chocolate with cocoa butter alternatives - Wan Ibadullah, Wan Zunairah; Han, Tan Zi; Xuan, Chung Ying; Ahmad, Nur Fatin Natasya; Ishak, Izzreen; Khaironi, Johari; Mustapha, Nor Afizah; Ismail-Fitry, Mohammad Rashedi; Sukor, Rashidah; Zainal Abedin, Nur Hanani; Mahmud Ab Rashid, Nor-Khaizura (Hibiscus Publisher, 2024)
An emulsifier is incorporated to delay the fat bloom formation and improve the overall quality of dark chocolate. This study aims to investigate the effects of different emulsifiers on the physical properties and stability of fat bloom in dark chocolate with cocoa butter alternatives (CBAs). Dark chocolate formulations were prepared containing different emulsifiers like lecithin, glycerol monostearate and a combination of both with CBAs like cocoa butter substitute (CBS) and cocoa butter replacer (CBR). Physical property analyses included hardness, snap texture, melting behaviour, pH, and water activity. The whiteness index was used to measure fat maturity. The results showed that the addition of lecithin, CBS, and CBR decreased the hardness value. Meanwhile, samples of chocolate formulation with the addition of glycerol monostearate (CB+GMS), and chocolate formulation with the addition of lecithin and glycerol monostearate (CB+2E), increased the hardness and snap texture. Besides, CBR increased the peak temperature, and emulsifiers increased the peak temperature in samples with CB and CBR while decreasing the melting enthalpy. Furthermore, the addition of CBA and emulsifiers improved the stability of the fat bloom. Therefore, mixed emulsifiers, which have favourable physical properties and higher fat bloom stability, are ideal for use in chocolate production. CBAs have the potential for practical application in chocolate production to improve fat bloom stability.